2019
DOI: 10.1111/cpr.12602
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different strategies for scalable production and proliferation of human myoblasts

Abstract: Objectives: Myoblast transfer therapy (MTT) is a technique to replace muscle satellite cells with genetically repaired or healthy myoblasts, to treat muscular dystrophies. However, clinical trials with human myoblasts were ineffective, showing almost no benefit with MTT. One important obstacle is the rapid senescence of human myoblasts. The main purpose of our study was to compare the various methods for scalable generation of proliferative human myoblasts. Methods:We compared the immortalization of primary my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Transduction of human myoblasts with human telomerase reverse transcriptase (hTERT) is not sufficient to immortalize these cells 7 . Even though overexpression of cyclin-dependent kinase 4 (CDK4) or cyclin D1 with hTERT could result in myoblasts capable of extensive proliferation, these cells have compromised myogenic differentiation potential 7 , 8 . Recent advances in deriving myogenic cells from induced human pluripotent stem cells (hiPSCs) may provide opportunities to address the limited availability of human myogenic cells 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Transduction of human myoblasts with human telomerase reverse transcriptase (hTERT) is not sufficient to immortalize these cells 7 . Even though overexpression of cyclin-dependent kinase 4 (CDK4) or cyclin D1 with hTERT could result in myoblasts capable of extensive proliferation, these cells have compromised myogenic differentiation potential 7 , 8 . Recent advances in deriving myogenic cells from induced human pluripotent stem cells (hiPSCs) may provide opportunities to address the limited availability of human myogenic cells 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…To address this question, we used young and old primary adult human skeletal muscle (HSKM) progenitors to screen for a variety of embryonically regulated factors that are not lineage‐specific, to biomimic the foetal growth phase. We defined ‘young’ as <5 population doublings, and ‘old’ as more than 20 population doublings, based on prior experience with replicative senescence 46 . First, we found that old progenitors, compared with progenitors, showed significantly higher levels of cell cycle inhibitors such as p21 WAF1 , p27 KIP1 , and p16 INK4a (Figure 1A).…”
Section: Resultsmentioning
confidence: 95%
“…Differentiation was initiated by replacing growth media with differentiation medium, comprising of DMEM/F‐12, 2% KnockOut Serum Replacement (Gibco), 1% L‐glutamine (Gibco) and 1% penicillin‐streptomycin (Gibco), when the young adult HSKM progenitors were 80%–100% confluent. These young adult HSKM progenitors were previously validated to be 100% MYOD1 + during the proliferative stage, with robust expression of myogenic markers after differentiation 46 …”
Section: Methodsmentioning
confidence: 99%
“…It is a known fact that in the early stages of myoblast differentiation, the MyoD+/MYOG+ myocytes begin to accumulate muscle-specific ACTA1 and MYH3. Subsequently, myocytes may fuse, forming α-actinin+/MYOG+ multinucleated myotubes, and finally, muscle fibers [ 65 ].…”
Section: Discussionmentioning
confidence: 99%